Eficácia da Terapia fotodinâmica em modelo murino de candidíase oral e efeito genotóxico em células de Candida albicans - Carmello, Juliana Cabrini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study evaluated the efficacy of photodynamic therapy (PDT) in the inactivation of C. albicans in a murine models of oral candidosis. Additionally, this study evaluated the poetencial of PDT to promote DNA damage of fungal cell. For this purpose, three studies were conducted: 1. Evaluated the photodynamic effect of chloro-aluminum phthalocyanine encapsulated in cationic nanoemulsions (ClAlP NE) to inactivate Candida albicans in a murine model of oral candidiasis. 2. Evaluated the photoinactivation (PDT) of Candida albicans in a murine model of oral candidosis, mediated by Photodithazine® (PDZ). 3. Evaluated the potential of PDT mediated by Curcumin (CUR) associated with the blue LED in causing DNA damage of C. albicans. In the first study, 75 6-week-old female Swiss mice were immunosuppressed and inoculated with C. albicans to induce oral candidiasis. PDT was performed on the tongue by the application of the photosensitizers and LED light (100 J cm-² - 660 nm). Next, microbiological evaluation was carried out by recovering C. albicans from the tongue via colony forming units (CFU mL-1). Then, the animals were sacrificed and the tongues were surgically removed for histological analysis and analysis of inflammatory cytokines expression (IL-1, TNF-α and IL-6) by RT-qPCR. Data were analyzed by ANOVA test. ClAlP NE-mediated PDT was able to reduce C. albicans recovered from the tongue (2.26 log10) when compared with control (p<0.05). ClAlP DMSO-mediated PDT did not present antifungal activity. Histological analysis revealed that PDT did not promote adverse effects on the tongue tissue. PDT mediated by both photosensitizers induced the TNF-α expression when compared with control (P<0.05). ClAlP mediated by PDT induced the expression of inflammatory cytokines, TNF-α, irrespective of the drug system delivery used. In the second study, a new murine model of oral...(Complete abstract electronic access below)

O presente estudo avaliou a eficácia da terapia fotodinâmica (PDT) na inativação de Candida albicans em modelos murino de candidíase oral. Adicionalmente, este estudo avaliou se a PDT causa danos ao núcleo da célula fúngica. Dessa forma, foram conduzidos três estudos: 1. Avaliou a eficácia da cloro-alumínio-ftalocianina encapsulado em nanoemulsão catiônica (ClAlP NE) na inativação de Candida albicans presente em modelo murino de candidíase oral; 2. Avaliou a eficácia da PDT mediada pelo Photodithazine®(PDZ) como tratamento para candidíase oral induzida; 3. Avaliou o potencial da inativação fotodinâmica (PDT) mediado pelo fotossensibilizador (PS) Curcumina (CUR) associado ao LED azul em causar danos no DNA de C albicans. No estudo 1, 75 camundongos fêmeas com 6 semanas foram imunossuprimidos e inoculados com C. albicans para induzir candidíase oral. A PDT foi realizada sobre a língua pela aplicação dos fotossensibilizadores ClAlP NE ou ClAlP DMSO e luz LED (100 J/cm2 - 660 nm). Em seguida, a avaliação microbiológica foi realizada por meio da recuperação de C. albicans da língua dos animais. Diluições seriadas foram realizadas, as colônias viáveis foram quantificado e o número de UFC mL determinado. Os animais foram sacrificados 24 horas após a PDT e as línguas foram removidas cirurgicamente para análise histológica e para análise de expressão de citocinas pró e antiinflamatórias (IL-1, TNF-α e IL-6) por ensaio de RT-qPCR. Os dados foram analisados por One-Way ANOVA. A PDT mediada por ClAIP-NE reduziu 2,26 log10 da viabilidade celular de C. albicans em comparação ao grupo controle (p <0,05). A PDT mediada por ClAlP DMSO não apresentou atividade antifúngica. A análise histológica revelou que a PDT não promoveu efeitos adversos sobre o tecido língual dos animais. A terapia mediada por ambos os fotossensibilizadores induziu a expressão... (Resumo completo, clicar acesso eletrônico abaixo)
Effectiveness of photodynamic therapy in a murine model of oral candidiasis and genotoxic effect of Candida albicans cells
Keywords: Candida albicans; Candidíase bucal; Fotoquimioterapia; Toxicologia genética; Oral candidiase; Photochemotherapy